Estrone-3-Sulfate Stimulates the Proliferation of T47D Breast Cancer Cells Stably Transfected With the Sodium-Dependent Organic Anion Transporter SOAT (SLC10A6) - Karakus, Emre; Zahner, Daniel; Grosser, Gary; Leidolf, Regina; Gundogdu, Cemal; Sánchez-Guijo, Alberto; Wudy, Stefan A.; Geyer, Joachim (Frontiers in Pharmacology, 2018)
Estrogens play a pivotal role in the development and proliferation of hormone-dependent breast cancer. Apart from free estrogens, which can directly activate the estrogen receptor of tumor cells, sulfo-conjugated steroids that maintain high plasma concentrations even after menopause first have to be imported into tumor cells by carrier-mediated uptake and then can be cleaved by the steroid sulfatase to finally activate estrogen receptors and cell proliferation. In the present study, expression of the sodium-dependent organic anion transporter SOAT was analyzed in breast cancer and its role for hormone-dependent proliferation of T47D breast cancer cells was elucidated. The SOAT protein was localized to the ductal epithelium of the mammary gland by immunohistochemistry. SOAT showed high expression in different pathologies of the breast with a clear ductal localization, including ductal hyperplasia, intraductal papilloma, and intraductal carcinoma. In a larger breast cancer cDNA array, SOAT mRNA expression was high in almost all adenocarcinoma specimen, but expression did not correlate with either the estrogen receptor, progesterone receptor, or human epidermal growth factor receptor 2 status. Furthermore, SOAT expression did not correlate with tumor stage or grade, indicating widespread SOAT expression in breast cancer. To analyze the role of SOAT for breast cancer cell proliferation, T47D cells were stably transfected with SOAT and incubated under increasing concentrations of estrone-3-sulfate (E1S) and estradiol at physiologically relevant concentrations. Cell proliferation was significantly increased by 10-9 M estradiol as well as by E1S with EC50 of 2.2 nM. In contrast, T47D control cells showed 10-fold lower sensitivity to E1S stimulation with EC50 of 21.7 nM. The E1S-stimulated proliferation of SOAT-T47D cells was blocked by the SOAT inhibitor 4-sulfooxymethylpyrene. In conclusion: The present study clearly demonstrates expression of SOAT in breast cancer tissue with ductal localization. SOAT inhibition can block the E1S-stimulated proliferation of T47D breast cancer cells, demonstrating that SOAT is an interesting novel drug target from the group of E1S uptake carriers for anti-proliferative breast cancer therapy.